Tied, leading, or trailing: How do extra-lightweight judokas adjust their attacks to secure victory? - Tsai, M.; Chen, Y. (International Journal of Performance Analysis in Sport, 2025)
Judo is an open-skill combat sport requiring continuous adaptation to dynamic match conditions, yet how judokas adjust their attacking actions based on score status (tied, leading, or trailing) remains unclear. To address this gap, we recorded 5,021 positive actions (423 scoring and 4,598 non-scoring attacks) from 374 matches across 11 Grand Slam during 2023 and 2024, using notational analysis. Generalized Estimating Equations examined how the number and effectiveness of attacks, and specific techniques, under different score statuses influenced match outcomes. Results showed that both the number (ORs >1.22) and effectiveness (ORs >1.08) of attacks predicted victory when judokas were tied or leading, highlighting the importance of offensive persistence. When trailing, only the effectiveness of attacks (OR=1.10) was a significant predictor, emphasising execution quality. Technique preferences varied by score status: when tied, more leg (OR=1.17) and ground techniques (OR=1.94) increased the probability of winning; when leading, more hand (OR=1.28) and ground techniques (OR=5.90). Whereas when trailing, no techniques predicted outcomes. Crucially, across all score statuses, higher technique effectiveness increased the probability of winning. These findings provide insights into elite judo and can inform targeted training to enhance performance.